High-κ Wide-Gap Layered Dielectric for Two-Dimensional van der Waals Heterostructures - Söll, Aljoscha; Lopriore, Edoardo; Ottesen, Asmund; Luxa, Jan; Pasquale, Gabriele; Sturala, Jiri; Hájek, František; Jarý, Vítězslav; Sedmidubský, David; Mosina, Kseniia; Sokolović, Igor; Rasouli, Saeed; et al. (ACS nano, 2024)
van der Waals heterostructures of two-dimensional materials have unveiled frontiers in condensed matter physics, unlocking unexplored possibilities in electronic and photonic device applications. However, the investigation of wide-gap, high-κ layered dielectrics for devices based on van der Waals structures has been relatively limited. In this work, we demonstrate an easily reproducible synthesis method for the rare-earth oxyhalide LaOBr, and we exfoliate it as a 2D layered material with a measured static dielectric constant of 9 and a wide bandgap of 5.3 eV. Furthermore, our research demonstrates that LaOBr can be used as a high-κ dielectric in van der Waals field-effect transistors with high performance and low interface defect concentrations. Additionally, it proves to be an attractive choice for electrical gating in excitonic devices based on 2D materials. Our work demonstrates the versatile realization and functionality of 2D systems with wide-gap and high-κ van der Waals dielectric environments.
Keywords: excitons; dielectric; high-k; crystal synthesis; field-effect transistors; two-dimensional materials; heterostructures